(untitled) (International Journal of Food and Nutritional Sciences, 2023)
“The success of a player depends upon the physique and the training she gets. According to Hirata ’(1979) the best factors to be used as screening tests, may be the age and physique because when the training methods are equivalent to all, the suitable physique will be most important i. e. if a person who has a suitable physique and takes best training may become a champion. The relationship of body structure and body composition to physical performance in volleyball players has been studied by many authors (Lamp; 1954; Hirata, 1966; Gladden and Colacino, 1978; Spence et aL, 1980; Morrow et al., 1979; Hosler et al., 1978;Sodhi, 1976; Grewal and Bhatnagar, 1983). But there is little data on university level female players in volleyball, however, Grewal & Sidhu (1983) suggested the selection of female volleyball players with reference to Ponderal Index.